Two species of Nilothauma Kieffer (Diptera, Chironomidae) from Japan, with description of a new species - Niitsuma, Hiromi (Zootaxa, 2016)
The male and female adults and pupa of Nilothauma niidaense n. sp. are described and illustrated on the basis of the material collected from a fontal stream in Fukushima Prefecture, Japan. N. sasai Adam & Sæther is treated as a junior synonym of N. hibaratertium Sasa, of which the male is redescribed. The Adam & Sæther key to Nilothauma males is revised.